Psychosocial Influences on Children’s Food Consumption - Roberts, M.; Pettigrew, Simone (John Wiley & Sons, Inc., 2013)
This exploratory study generated a grounded theory of factors influencing children’s diets, particularly those that contribute to suboptimal eating and ultimately child obesity. The study involved 124 children (aged 6–12 years) and 39 of their parents from three separate junior schools (including a lower, middle, and higher socioeconomic school). Research methods included (i) interviews with children and parents and (ii) observations, drawings, and lunchbox audits with children. The findings suggest that children and parents prioritize psychosocial needs overphysiological needs during food selection and consumption. This tendency toward psychosocial eating appears to be strongly reinforced by food advertising.